New archaeological excavations in the Lavacello area in Calvatone (CR) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The new archaeological investigations carried out in the Lavacello area in Calvatone (CR) have brought to light traces of a long ancient presence ranging from the Preroman Age to the Renaissance Age. The protohistoric and roman evidence provide interesting information on the methods of exploitation of the territory and the occupation of the area in the phases preceding the first frequentation of the nearby site of Calvatone / Bedriacum.
Keywords: Lavacello; Calvatone; Water channels; Iron Age; amphorae